[BI019] Molecular Cloning And Characterisation Of The 5 -Untranslated Region And Promoters In Human Peroxisome Proliferator-Activated Receptor Alpha (hPPARα). - Chew, Choy Hoong; Najimudin, Nazalan; Tengku-Muhammad, Tengku Sifzizul (2004)

(untitled)
The peroxisome proliferator activated receptors (PPARs) are members of the nuclear hormone receptor gene superfamily of ligandactivated transcription factors [Issemann and Green, 1990].